KEGIATAN SIKAP PEDULI KEBERSIHAN SEBAGAI UPAYA MENANGGULANGI AIR LAUT DAN PESISIR LAUT YANG KOTOR AKIBAT SAMPAH - Suwestian, M.Firdaus; Fathulliansyah, Noor; Sihombing, David Bastian; Herawati, Susi; Prihatin, Prihatin (Akademi Maritim Nusantara Banjarmasin, 2025)
Abstract Cleanliness is a human effort to maintain oneself and the environment from all that is dirty and vile in order to realize and preserve a healthy and comfortable life. Cleanliness is a prerequisite for achieving health, and health is one of the factors that can bring happiness. Conversely, dirtiness not only destroys beauty but can also cause various diseases, and illness is one of the factors that lead to suffering. Method of implementing community activities titled